تحليل حاجات طلاب االلغة العربية بوصفها لغة ثانية في المعهد الإِسلامي الصيني في كونمينغ - خو، ون خوي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research aims at analyzing the special needs of the students of the Chinese Islamic Institute in Kunming. The students of this institute are from China, and aim to specialize in Arabic and Islamic studies. And they study Arabic as a foreign language. These students do not want to know the Arabic language in all its aspects, but look for limited purposes and identify them in their university studies under the specialization they wish to attend (Arab or Islamic studies). The researcher considered the need to identify the needs of these students; to help officials in building a curriculum that covers the purposes of this community, and this research is based on analytical descriptive descriptive method, to study what has been done in this field of theoretical and field research; And 100 students; to find out their needs. The study came out with a number of facts. The most important of these facts are: In their daily lives, students need Arabic language for dialogue with colleagues and friends. In the academic field, the respondents showed their urgent need for Arabic to understand lectures. Finally, in their future life, the study revealed that students need Arabic to chat with colleagues at work, as well as to write letters and translate them from Arabic to Chinese.